Procurement Contract Management and Sustainable Performance of State Corporations in Kenya - Gatari , Catherine Njoki; Shale, Noor Ismail; Osoro, Anthony Osoro (International Journal of Supply Chain and Logistics, 2022)
Purpose: The purpose of this study was to establish the effect of procurement contract management on sustainable performance of state corporations in Kenya. Methodology: The research design used in this research was mixed-methods research design. The study focused on 187 state corporation as the target population. Census was applied where all state corporations were surveyed and purposive sampling was used to pick the finance manager and the procurement manager which resulted to 374 respondents. The study main source of data was primary data which was gathered using research questionnaires. The gathered data was assessed with the help of Statistical Package for Social Sciences (SPSS) Version 28. The study carried out both descriptive and inferential analysis to draw conclusions. Results: The inferential analysis results revealed that procurement contract management had a significant and positive influence on the sustainable performance of state corporations in Kenya at p<0.05. This indicates that contract preparation, contract administration, contract control and monitoring and contract conflicts resolution mechanisms are crucial drivers of sustainable performance of an organization. The model summary found that a unit change in procurement contract management may account for a variability of 45.1% in a firm's sustainable performance. The R value for the model was 0.670 and the R2 was 0.451. This was a sign that the model was appropriate for establishing the link between procurement contract management and sustainable performance and, as a result, for drawing the conclusions and suggestions from the study. Unique Contribution to Theory, Practice and Policy: While the existing theory of public contracts used in this study was validated, the study recommends that the government through the appropriate regulatory agencies and the management of public procuring entities have the mandate to make sure that appropriate oversight of the management of contracts in state corporations is carried out as a means of ensuring accountability and justice throughout the entire process. According to the study, policymakers and state regulatory organizations should take the lead in making sure that contracts are properly documented and that they are diligently and effectively managed to ensure full adherence to the rules and regulations.